THE EFFECT OF WORK ENVIRONMENT, WORK MOTIVATION, AND WORK DISCIPLINE ON PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN ASN EMPLOYEES AT RSUD DR. R.M DJOELHAM BINJAI - Manurung, Eriyanti Agustina; Siregar, Robert Tua; Rostina, Cut Fitri (Mount Hope Economic Global Journal, 2025)
This research aims to analyze the influence of work environment, work motivation, and work discipline on the performance of civil servants (ASN) at RSUD Dr. R.M. Djoelham Binjai, with job satisfaction as an intervening variable. The study focuses on understanding how these factors affect employee performance, while also considering job satisfaction as a crucial mediator. The research utilizes a quantitative approach, with data collected through surveys administered to 57 ASN employees from the nursing department at RSUD Dr. R.M. Djoelham Binjai. Data analysis was performed using statistical methods such as validity and reliability tests, assumption tests (normality, multicollinearity, and heteroscedasticity), and hypothesis testing, including the Sobel test for mediation analysis. The findings of this study reveal that both work environment and work discipline have a positive and significant impact on employee performance, with job satisfaction playing a key role in mediating these effects. Furthermore, work motivation, while having a significant positive influence on job satisfaction, did not have the same direct impact on performance. The study highlights the importance of creating a supportive work environment and fostering strong work discipline to enhance the overall performance of ASN employees. These results provide practical implications for RSUD Dr. R.M. Djoelham Binjai's management in improving the work environment, employee motivation, and discipline, which in turn would contribute to better job satisfaction and enhanced organizational performance.